1982
DOI: 10.1007/bf01655365
|View full text |Cite
|
Sign up to set email alerts
|

The Radiologist's role in acute endocrine problems

Abstract: Ultrasound and computed tomography have had an enormous impact on the imaging procedures used in the detection of tumors of the parathyroids, pancreas, and adrenals. Ultrasound is now the examination of choice in localizing parathyroid adenomas in the neck prior to cervical exploration or after unsuccessful exploration. Its role as a screening test in patients without biochemical confirmation of hyperparathyroidism awaits further study. Computed tomography is useful in identifying mediastinal parathyroid adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Hypercalcemia is generally reversed in 90-95% of these cases [15][16][17]. It has been questioned if this result could be improved by a preoperative location of enlarged glands [4,5]. The benefit of ultrasound with respect to surgical success rates has not been addressed in the present investigation since this has to be decided by studies of extensive patient materials.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hypercalcemia is generally reversed in 90-95% of these cases [15][16][17]. It has been questioned if this result could be improved by a preoperative location of enlarged glands [4,5]. The benefit of ultrasound with respect to surgical success rates has not been addressed in the present investigation since this has to be decided by studies of extensive patient materials.…”
Section: Resultsmentioning
confidence: 97%
“…Ultrasonic examination of the parathyroid glands has attracted considerable interest in recent years for its ability to locate enlarged parathyroid glands prior to surgical therapy [1][2][3][4][5][6]. The identity of ultrasonically detected tumors may be difficult to establish unequivocally from the echogram [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen percent of these tumors have sizes less than 1 cm and cannot be visualized preoperatively, despite good diagnostic procedures [8,11]. Ten percent of insulinomas are neither visible nor palpable on bimanual exploration of the pancreas [7,37,38]. These diagnostic difficulties are due to the cephalic site of the tumor and its deep location within the gland [19].…”
Section: Discussionmentioning
confidence: 99%
“…There are three methods for determining tumor localization during surgery: inspection, palpation, and IOUS. The literature suggests that approximately 10% of insulinomas are neither visible nor palpable in bimanual examinations of the pancreas , so IOUS needs to be performed to raise this to 100% . One review showed that the range of sensitivity of inspection and palpitation combined was 41.7%–96.4%, and it was 62.5%–100% for IOUS .…”
Section: Discussionmentioning
confidence: 99%